2023
DOI: 10.1038/s41467-023-36693-9
|View full text |Cite
|
Sign up to set email alerts
|

Structural mechanism for inhibition of PP2A-B56α and oncogenicity by CIP2A

Abstract: The protein phosphatase 2A (PP2A) heterotrimer PP2A-B56α is a human tumour suppressor. However, the molecular mechanisms inhibiting PP2A-B56α in cancer are poorly understood. Here, we report molecular level details and structural mechanisms of PP2A-B56α inhibition by an oncoprotein CIP2A. Upon direct binding to PP2A-B56α trimer, CIP2A displaces the PP2A-A subunit and thereby hijacks both the B56α, and the catalytic PP2Ac subunit to form a CIP2A-B56α-PP2Ac pseudotrimer. Further, CIP2A competes with B56α substra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 67 publications
1
9
0
Order By: Relevance
“…4, C and E). These results supported the model that SET induced the PP2A-A repulsion from the chromatinassociated PP2A-C. Intriguingly, a recent paper has reported that another cellular PP2A inhibitor protein CIP2A also binds to the PP2A trimer and resulted in the dislocation of the PP2A-A subunit from the complex (55). The interesting parallel of this paper with our research indicated that PP2A-A repulsion could be common mechanistic basis for PP2A inhibition by its inhibitory proteins.…”
Section: Set-ko Did Not Alter the Tss Occupancy Of Cdk9 Or Pp2a-c But...supporting
confidence: 90%
“…4, C and E). These results supported the model that SET induced the PP2A-A repulsion from the chromatinassociated PP2A-C. Intriguingly, a recent paper has reported that another cellular PP2A inhibitor protein CIP2A also binds to the PP2A trimer and resulted in the dislocation of the PP2A-A subunit from the complex (55). The interesting parallel of this paper with our research indicated that PP2A-A repulsion could be common mechanistic basis for PP2A inhibition by its inhibitory proteins.…”
Section: Set-ko Did Not Alter the Tss Occupancy Of Cdk9 Or Pp2a-c But...supporting
confidence: 90%
“…Several open questions remain in the context of this study. The factors underlying the pathological suppression of PP2A activity need to be explored in greater detail in fibroblasts from IPF subjects, particularly the interplay of B-subunit expression, C-terminal leucine carboxymethylation, and expression of endogenous PP2A inhibitor expression (for a recent study relevant to this, see Pavic et al). The expression of one endogenous inhibitor of PP2A, CIP2A, is reported to be sensitive to the previously published tricyclic sulfonamide compounds; , however, we observed no CIP2A changes or changes in other endogenous PP2A inhibitors in fibroblasts from IPF patients (see Figure S3A).…”
Section: Discussionmentioning
confidence: 99%
“…In support of our observations, the gene cell proliferation regulating inhibitor of protein phosphatase 2A (CIP2A) is fourth on the list of BOD1L1 co-dependent genes from the CRISPR screens displayed in the Cancer Dependency Map Project 30,31 . CIP2A is a functional oncogene that inhibits the PP2A complex in various contexts including the DNA damage response, mitotic entry and mitotic progression by replacing the structural subunit of the PP2A complex, blocking phosphatase function 32,33 . Thus, the co-dependency between the two genes suggests that cell lines that are dependent on BOD1L1 for regulating phosphatase activity do not tolerate the loss of another gene that negatively regulates PP2A.…”
Section: Discussionmentioning
confidence: 99%